An Inelastic Theoretical Model regarding the Load-Carrying Capacity of PSL Bending Component - Baolu Sheng; Yuling Bian; Dong He; Aiping Zhou (Advances in Civil Engineering)
Parallel strand lumber (PSL) is an attractive structural wood composite which may have prospective use in building constructions. Conducting nonlinear analysis for the bending of PSL beams is a critical step in the determination of ultimate strength and deflection of them, which is an essential requirement of the building design philosophy based on probability of ultimate state. For the purposes of this article, an inelastic theoretical model regarding the load-carrying capacity of the PSL bending component has been developed. Based on the uniaxial loading tests, the stress-strain behaviors of PSL composite in the grain direction were measured. 4-point bending experiments were also performed in this study to investigate the failure mechanism of the PSL components. The results show that the tensile stress-strain relationship of PSL materials in the grain direction remains linear until breaking, while the compressive stress-strain relationship exhibits nonlinear characteristics once the compressive stress exceeds the proportional limit, which can be expressed by a quadratic polynomial. The failure mode of the PSL beam can be summarized that the fibres in the top of the broken section were buckling and those in the bottom of the section were broken when failure occurred. Significant nonlinear behavior was exhibited based on the load-deflection curves of the PSL beams. To predict the nonlinear bending performance of the PSL beams, a theoretical model that could consider the nonlinear stress-strain relations of PSL and predict the damage modes of the PSL beams was developed. Well agreements can be observed between the results of calculations and experiments.